Crowdfunding or traditional mode? Strategy choices in product selling. (April 2023) - Xu, Shengshuo; Ling, Liuyi; Du, Shaofu; Liu, Lindong
Abstract: This study examines two selling strategies, namely, crowdfunding and traditional selling. Under traditional selling, the production behavior of the creator occurs before the purchases by consumers. In this case, the demand is uncertain, and the creator's production behavior is affected by the initial funding level. Under crowdfunding, the production behavior of the creator comes after the consumers have provided funding. In this case, consumers bear the opportunity cost, and the campaign succeeds (leading to production) only when the market demand exceeds a threshold value. In the basic model, we investigate the pricing strategy and the expected profit of the creator for each selling strategy. Our analysis reveals that crowdfunding dominates traditional selling when the creator's initial funding is low, or the unit production cost is high. We then generalize our models by considering product quality, providing main results consistent with those derived in the basic model but also revealing new and interesting insights. For example, in the case of endogenous product quality, the creator prefers a low production volume under traditional selling, and the opportunity cost has a large (small) impact on crowdfunding (traditional selling). Finally, we examine several extensions to our studies, including adopting Keep-It-All model for crowdfunding, the case involving multiple potential consumers, and the case where the consumer's valuation follows a normal distribution. Our paper highlights that crowdfunding, as a method of collecting finance, is also advantageous for creators with sufficient initial funding under certain conditions. Conclusions from these investigations can guide creators during their sales planning. Highlights: Model and examine two selling strategies: crowdfunding and traditional selling. Guide the creator when choosing between crowdfunding and traditional selling. Investigate two selling strategies by taking the product quality into consideration. Provide several interesting extensions of the results.